Explorations about the Family's Role in the German Transplantation System: Epistemic Opacity and Discursive Exclusion. (2nd January 2022) - Hilbrich, Iris; Hansen, Solveig Lena
ABSTRACT: With regard to organ donation, Germany is an 'opt-in' country, which requires explicit consent from donors. The relatives are either asked to decide on behalf of the donors' preferences, if these are unknown or if the potential donor has explicitly transferred the decision to them. At the core of this policy lies the sociocultural and moral premise of a rational, autonomous individual, whose rights require legal protection in order to guarantee a voluntary decision. In concrete transplantation practices, the family plays an even more important role. Potential donors and their families decide while being embedded in relations, a point which does still not gain full recognition. This particular discrepancy between policy and practice creates conflicts, which remain taboos of academic inquiry and public discourse. Our analysis shows a plurality of the family's role in the transplantation process, which reveals an inner tension of the organ donation system. This tension provokes epistemic opacity on the one hand and different collective strategies as responses to discursive exclusion on the other. In future deliberations about organ donation, it is important to create spaces for open discussion, but also practices of communicative engagement, which take care of the needs and emotions attached to taboos.